2013
DOI: 10.7567/jjap.52.07hg01
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Convolutional Code in Multipath Underwater Acoustic Channel

Abstract: The forward error correction (FEC) is achieved by increasing redundancy of information. Convolutional coding with Viterbi decoding is a typical FEC technique in channel corrupted by additive white gaussian noise. But the FEC effectiveness of convolutional code is questioned in multipath frequency selective fading channel. In this paper, how convolutional code works in multipath channel in underwater, is examined. Bit error rates (BER) with and without 1/2 convolutional code are analyzed based on channel bandwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…It was concluded that other than BER improvements, the PAPR of an OFDM system is significantly reduced when ciphered BCH codes are utilized. Park et al [ 15 ] have assessed the forward error correction capabilities of convolutional codes of code rate in the presence of multipath in underwater acoustic channels. The authors suggest the proposed convolutional codes for OFDM in multipath channel without equalizers in a slow-moving scenario.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It was concluded that other than BER improvements, the PAPR of an OFDM system is significantly reduced when ciphered BCH codes are utilized. Park et al [ 15 ] have assessed the forward error correction capabilities of convolutional codes of code rate in the presence of multipath in underwater acoustic channels. The authors suggest the proposed convolutional codes for OFDM in multipath channel without equalizers in a slow-moving scenario.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Channel coding techniques such as forward error correction codes (FEC) have long been used for reliable transmission in wireless communication systems [ 14 , 15 ]. The data-rate is reduced due to the coding overhead and requires an increase in bandwidth.…”
Section: Introductionmentioning
confidence: 99%
“…Convolution codes and Reed Solomon block codes are commonly used for real-time underwater acoustic communication system due to their simplicity. These codes were still not adequate to satisfy the BER requirement [11, 12]. Space-time trellis codes, layered space-time codes, and their combinations scheme were developed for high reliability and high data rate communications [13].…”
Section: Introductionmentioning
confidence: 99%
“…The time diversity technique such as a convolution code(CC) and Reed-Solomon(RS) code has been applied in underwater acoustic communication systems [6][7][8]. The error correcting capability of CC is found to be better than RS in frequency non-selective multipath channel but vice versa in frequency selective channel.…”
Section: ⅰ Introductionmentioning
confidence: 99%